2016
DOI: 10.1002/acr.22695
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Interferon‐Inducible Protein IFI16 Correlates With Clinical and Serological Features in Rheumatoid Arthritis

Abstract: Objective. The interferon-inducible protein 16 (IFI16) has been detected in sera from patients with autoimmune/ inflammatory diseases, but not in healthy subjects. This leaking leads to loss of tolerance toward this self-protein and the development of autoantibodies. In this study, clinical significance of both IFI16 protein and anti-IFI16 antibodies in rheumatoid arthritis (RA) was investigated. Methods. IFI16 protein and anti-IFI16 antibody levels were assessed by enzyme-linked immunosorbent assay in serum s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 25 publications
(47 reference statements)
1
26
0
Order By: Relevance
“…The inflammatory context in which an intracellular protein is released is thought to be one of the mechanisms leading to the breakdown of tolerance and the recognition of self‐antigens; this hypothesis could explain the antibody response against IFI16 observed in PsA and Pso, particularly with the intriguing observation of a prevalent IgA response compared to IgG response in PsO versus PsA. As previously mentioned, and different from PsA (with anti‐IFI16 IgG titres slightly increased in subjects with elevated CRP levels), anti‐IFI16 antibodies are not correlated to RA activity, but rather with serum autoantibody positivity, while no association between anti‐IFI16 and disease activity or erosions has been found . In SLE, anti‐IFI16 antibodies were first reported to be associated with anti‐double‐stranded DNA antibodies , but this was not confirmed by our group .…”
Section: Discussionmentioning
confidence: 95%
“…The inflammatory context in which an intracellular protein is released is thought to be one of the mechanisms leading to the breakdown of tolerance and the recognition of self‐antigens; this hypothesis could explain the antibody response against IFI16 observed in PsA and Pso, particularly with the intriguing observation of a prevalent IgA response compared to IgG response in PsO versus PsA. As previously mentioned, and different from PsA (with anti‐IFI16 IgG titres slightly increased in subjects with elevated CRP levels), anti‐IFI16 antibodies are not correlated to RA activity, but rather with serum autoantibody positivity, while no association between anti‐IFI16 and disease activity or erosions has been found . In SLE, anti‐IFI16 antibodies were first reported to be associated with anti‐double‐stranded DNA antibodies , but this was not confirmed by our group .…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, smoking is strongly associated with the development of ILD. Therefore, smokers are more likely to be seropositive and more often develop RA-ILD (23,24). However, it is conceivable that other mechanisms could be responsible for aberrant peptide citrullination, otherwise the presence of ACPA in non-smokers could not be explained.…”
Section: N Discussion and Conclusionmentioning
confidence: 99%
“…Some studies, in fact, suggested a protective rather than proinflammatory role of anti-IFI16 autoantibodies (8,9). On the contrary, there is consistent evidence for a pathogenic role of IFI16 protein in triggering and perpetuating inflammation in some chronic inflammatory and autoimmune rheumatic disorders (10).…”
Section: To the Editormentioning
confidence: 99%